On the Nonlinear Thermomechanical Analysis of a Stayed-Beam Having Fractional Viscoelastic Properties in Complex Environment - Yaleu, T.B. Djuitchou; Fankem, E.R.; Nbendjo, B.R. Nana (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, the nonlinear thermomechanical analysis of a stayed-beam made with fractional viscoelastic materials subjected to wind load and platoon motion loads under thermal conditions is investigated. Using Newton's second law of motion, the equation of dynamics is derived and reduced to generalized modal forms by applying the Galerkin methods. In the first vibration mode, the analytical study is conducted via multi-scale methods. Following this analytical procedure, the appearance conditions of various types of bifurcation are obtained using linear analysis; the periodic solutions are obtained using nonlinear analysis; then, the effect of fractional viscoelasticity, thermal variation and load spacing on the dynamics of the structure are explained numerically. It is found that, taking into account thermal loads due to temperature change in the environment, material properties and mechanical loads, many complex phenomena or loss of stability depending on the type of external loads can occurs. Thus, the advantageous effects of viscoelastic fractional derivative material, thermal and load spacing are established and it is also found that, depending on the type of loads, the fractional order changes the effect of thermal loads on the structure.